KETERGANTUGAN SCROLLING TIKTOK DALAM PEMBENTUKAN FENOMENA BRAIN ROT - Alyah Khaerunnisa; Devi Purnamasari (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2026)
TikTok is a social media platform widely used for entertainment, allowing users to create, share, and consume audiovisual content through short-form videos. In Indonesia, TikTok has experienced significant growth, with its users reaching 194 million. In 2024, Indonesian TikTok users were also reported to spend more than 44 hours per month on the platform. This high level of use indicates Generation Z’s strong engagement with fast, brief, and repetitive content. This study examines TikTok scrolling dependency in the formation of the brain rot phenomenon among Generation Z by applying Media Ecology Theory and Media Dependency Theory. This research employs a qualitative approach with a phenomenological method to understand users’ experiences in consuming TikTok content. Data were collected through in-depth interviews with five active Generation Z TikTok users. The findings reveal that dependency develops through repeated app use, difficulty controlling usage duration, and the tendency to rely on TikTok as instant entertainment. This condition contributes to brain rot, reflected in decreased cognitive focus, delayed activities, mood changes, and disrupted time management. The study concludes that brain rot is shaped by TikTok’s media characteristics and users’ dependence on fast digital content. Digital literacy and selfcontrol are necessary to promote wiser social media use.